Gender equality in the editorial process of public health journals from the American continent - Ramirez Soto, Max Carlos (2020)
Despite an increase in the participation of women in scientific publications, a gender gap persists with a predominantly male authorship, especially in high-impact factor journals. Similarly, there is a lower proportion of women participating as peer reviewers or editors for journal publications.